Upstream anticoagulation for patients with ST‐elevation myocardial infarction undergoing primary percutaneous coronary intervention: Insights from the TOTAL trial. Issue 3 (15th October 2019) - Cantor, Warren J.; Lavi, Shahar; Džavík, Vladimír; Cairns, John; Cheema, Asim N.; Della Siega, Anthony; Moreno, Raul; Stankovic, Goran; Kedev, Sasko; Natarajan, Madhu K.; Levi, Yaniv; Yuan, Fei; et al.
Abstract: Objectives: To assess the relationship between preprocedural anticoagulation use and clinical and angiographic outcomes. Background: For patients with ST‐elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI), the optimal timing of anticoagulant administration remains uncertain. Methods: Patients enrolled in the TOTAL trial were stratified based on whether or not they had received any parenteral anticoagulant prior to randomization and PCI. Baseline and procedural characteristics were compared. For one‐year clinical outcomes, Cox proportional modeling adjusted on a propensity score was used to analyze differences between groups. Angiographic endpoints were analyzed by logistic regression models adjusted for propensity scores. Results: In the trial, 10, 064 patients were enrolled and underwent PCI. Preprocedural anticoagulation was used in 6, 381 patients (63%).The most common anticoagulant was intravenous unfractionated heparin (5, 188, 81%). Patients who received preprocedural anticoagulation had higher rates of TIMI‐2‐3 or TIMI‐3 flow and lower grades of thrombus prior to PCI. Pretreatment with anticoagulation was associated with lower use of bailout thrombectomy, GP IIb/IIIa inhibitors, and intra‐aortic balloon pump. After adjustment, preprocedural anticoagulation was associated with lower rates of CABG and minor bleeding at 1 year but there were no significant differences in death, stroke, recurrent MI, cardiogenic shock, or congestive heart failure. Conclusions: Preprocedural anticoagulation is associated with improved flow and reduced thrombus in the IRA prior to PCI, less bailout thrombectomy during PCI but no difference in death, recurrent infarction, or heart failure at 1 year.